2018
DOI: 10.1097/cco.0000000000000452
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation or low-level laser therapy in the management of cancer therapy-induced mucositis, dermatitis and lymphedema

Abstract: The article discusses LLLT/PBM mechanisms of action, dosimetry, and safety, and aims to identify some cancer treatment side-effects for which LLLT/PBM may prove to be effective (oral mucositis, radiation dermatitis, lymphedema). In addition, LLLT/PBM parameters for each of these complications are suggested and future research directions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 36 publications
1
35
0
6
Order By: Relevance
“…RD, OM, and LE involve inflammatory responses in both early and chronic phases with the expression of inflammatory cytokines (Interleukins (IL), tumor necrosis factor-α (TNF-α) and polarization macrophages ( 3 , 4 , 53 ).…”
Section: Influence Of Lllt At Cellular Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…RD, OM, and LE involve inflammatory responses in both early and chronic phases with the expression of inflammatory cytokines (Interleukins (IL), tumor necrosis factor-α (TNF-α) and polarization macrophages ( 3 , 4 , 53 ).…”
Section: Influence Of Lllt At Cellular Levelmentioning
confidence: 99%
“…Phototherapy with ultraviolet light has been used for many years in the treatment of psoriasis (1) or neonatal jaundice (2). Recently, with wider availability of instruments, PBM using low-level laser therapy (LLLT) has provided an exciting new frontier in the management of wound healing, pain, tissue swelling and particularly for oncology, the inflammatory conditions such as radiation dermatitis (RD), oral mucositis (OM) and lymphedema (LE) (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Also the potential application of PBM for management of xerostomia, dysgeusia, radiodermatitis, post-RT fibrosis, chronic oral graft-versus-host disease (GVHD), and breast cancer-related lymphedema has been reported. [10][11][12][13][14][15][16][17] The basic principle of supportive care in cancer is to provide effective management of complications of cancer treatment without compromising or inducing negative effects on oncology outcomes; also bearing in mind unwanted and dire consequences such as tumor persistence, new secondary tumors, or recurrence of the primary disease. Various in vitro studies have suggested that PBM may induce accelerated growth in some malignant cell lines and/or development of malignancy in dysplastic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, low‐level laser therapy (LLLT) has gained attention for the fibrosis treatment as a noninvasive and nonthermal method . LLLT typically delivers a wide range of wavelengths from 600 to 1,000 nm under 100 J/cm 2 using laser diodes or light‐emitting diodes (LEDs) . In particular, red and near‐infrared lights are often examined and used to aid wound healing to relieve acute or chronic pain and to reduce inflammation .…”
Section: Introductionmentioning
confidence: 99%